Productive Waqf as a Sustainable Financial Instrument in the Perspective of Islamic SDGs - Judijanto, Loso; Sarif, Akbar; Ariyanti, Rini (West Science Islamic Studies, 2025)
This paper explores the concept of productive waqf as a sustainable financial instrument within the framework of Islamic Sustainable Development Goals (Islamic SDGs). The literature review analyzes various scholarly works on productive waqf, focusing on its potential to generate income through investment in income-generating ventures, such as real estate and social enterprises. The review identifies key benefits of productive waqf, including its alignment with poverty alleviation, education, healthcare, economic empowerment, and environmental sustainability. Despite its potential, challenges such as legal barriers, governance issues, and public awareness remain significant obstacles. The paper highlights the need for regulatory reforms, professional management, and public education to unlock the full potential of productive waqf. It concludes that with proper reforms, productive waqf can play a pivotal role in achieving sustainable development goals within the Islamic context.